1979
DOI: 10.1007/bf01869257
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of membrane-bound (Na+−K+)-ATPase as revealed by trypsin digestion

Abstract: To distinguish ligand-induced structural states of the (Na+--K+)-ATPase, the purified membrane-bound enzyme isolated from rat kidneys was digested with trypsin in the presence of various combinations of Na+, K+, Mg++ and ATP. It was found that first the large and then the small polypeptide chain of the (Na+--K+)-ATPase was degraded, indicating that the lysine and arginine residues of the large chain are more exposed than are those of the small one. The (Na+--K+)-ATPase activity was inactivated in parallel with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…High-affinity binding of cardiac glycosides to (Na,K)-ATPase can be induced by different combinations of ligands, mainly Na + MgATP,Mg + Pi, and Mg + vanadate Albers et al, 1968;Sen et al, 1969;Post et al, 1969;Fortes, 1977;Wallick et al, 1977;1979;Hansen, 1979;Moczydlowski & Fortes, 1980). Measurements of the A 0 association and dissociation rate constants at 24 "C in the presence of these ligand combinations showed that the value of k,, was largest with vanadate (2.65 X lo4 M-' s-') and smallest with ATP (6.1 x 103 M-1 s-1 ), w hereas k,ff was largest with ATP (6.5 X s-l) and smallest with vanadate (1.97 X s-').…”
Section: Effect Of Ligands On Resonance Energy Transfer From a 0 To Lmentioning
confidence: 94%
See 1 more Smart Citation
“…High-affinity binding of cardiac glycosides to (Na,K)-ATPase can be induced by different combinations of ligands, mainly Na + MgATP,Mg + Pi, and Mg + vanadate Albers et al, 1968;Sen et al, 1969;Post et al, 1969;Fortes, 1977;Wallick et al, 1977;1979;Hansen, 1979;Moczydlowski & Fortes, 1980). Measurements of the A 0 association and dissociation rate constants at 24 "C in the presence of these ligand combinations showed that the value of k,, was largest with vanadate (2.65 X lo4 M-' s-') and smallest with ATP (6.1 x 103 M-1 s-1 ), w hereas k,ff was largest with ATP (6.5 X s-l) and smallest with vanadate (1.97 X s-').…”
Section: Effect Of Ligands On Resonance Energy Transfer From a 0 To Lmentioning
confidence: 94%
“…Na, K, ATP, vanadate, Mg + P¡ or Na + MgATP ± ouabain, and ouabain binding to the enzyme-vanadate complex. These ligands were used in the concentration ranges that have been shown to alter proteolytic patterns (Jorgensen, 1975;Castro & Farley, 1979; Koepsell, 1979) or the fluorescence of various probes (Fortes, 1977;Karlish, 1980;Moczydlowski & Fortes, 1981a;Hegyvary & Jorgensen, 1981;Taniguchi et al, 1983;Kapakos & Steinberg, 1982;Skou & Esmann, 1981). In addition, we tested the effect of K + Mg + ATP, which alters the susceptibility of the /3-subunit to proteolysis (Lo & Titus, 1978;Koepsell, 1979).…”
Section: [Ao]b = [Ao]t + [E]t + Kd-[([ao]t + [E]t + Ko)2 -4[ao]t[e]t]...mentioning
confidence: 99%
“…It is also pos sible that the opposing changes in the affini ties for K+ and ouabain reflect a more or less static modulation of the overall conformation of the a-subunit by its 3-subunit. On the other hand, ligand-induced changes in the suscepti bility of the 3-subunit to proteolytic enzymes [84,85] and in the distance between the car diac glycoside site and the 3 -subunit oligosac charides [86] imply that the 3 -subunit partici pates in conformational changes of the Na+/ K+-ATPase during ion transport.…”
Section: -Subunit Can Affect Catalytic Properties O F the Mature Somentioning
confidence: 99%
“…For these reasons, a is considered the catalytic subunit. The 0 subunit is a glycoprotein with a protein mass of 37 000-56000 daltons; 0 is close to the cardiac glycoside site of a (Hall & Ruoho, 1980) and appears to vary in sensitivity toward proteolysis depending on the presence of ligands of the enzyme (Lo & Titus, 1978;Koepsell, 1979). The function of 0 is unknown, although it has been postulated that 0 directs the insertion of a into the membrane (Sabatini et al, 1981).…”
mentioning
confidence: 99%